Effectiveness of Borage plus syrup on COVID-19 patients in intensive care units - Seyed MohammadReza Hashemian; Esmaeil Mortaz; Navid Shafigh; Shadi Ziaie; Hamidreza Jamaati; Morteza Hasheminik; Mehdi Jamalinik; Raziyeh Erfani; Batoul Khoundabi; Neda K. Dezfuli; Mohammad Varahram; Shahrzad Ahmadi; et al. (Frontiers in Nutrition, 2022)
IntroductionCOVID-19 (coronavirus disease-2019) still causes a high rate of death globally with no definite curative treatment described. The traditional plant Borage (Borago officinalis L.) is a good source of gamma-linolenic (GLA). We hypothesized that Borage plus syrup (BPS) would be beneficial in severe COVID-19 patients within an intensive care unit (ICU) setting.Materials and methodsA pilot single center, randomized trial with no placebo was undertaken. A total of 60 PCR-positive severe COVID-19 participants admitted to ICU from June 2020–December 2020 at Masih Daneshvari Hospital Tehran-Iran gave informed consent. The participants were randomly assigned to either Borage Plus Syrup (BPS, 5 ml for 5 days) (n = 30) or standard care (IFN-β and favipiravir) as a control group (n = 30). Pao2/Fio2, serum ferritin, CRP, bilirubin, IL-6, TNF-α, ALT, AST, PCT and serum IL-8 was measured upon admission and on release.ResultsAll the measured parameters decreased significantly with BPS treatment. In the control group, most parameters significantly improved apart from AST and PCT. In addition, the suppression of serum TNF levels in the BPS group was greater than that seen in the control group (P ≤ 0.05). Moreover, the length of ICU stay was significantly lower in the BPS group compared with the control group (P ≤ 0.05).ConclusionOur study shows that addition of BPS to the standard treatment regime of COVID-19 patients in ICU improved outcomes and reduced the length of ICU treatment. Natural products could be considered as new approaches for reducting the harmful consequences of COVID-19.